The Effectiveness of Behavioral Counseling with Shaping Technique to Increase The Feeling Guiltywhen of The Students Did A Mistake to Their Classmate - Norma Anggraini; I Ketut Dharsana; Ni Ketut Suarni (RedwhitePress)
The aims of this study is to find out the effectiveness of behavioral counseling with shaping technique to increase the feeling guilty behavior when the student did a mistake to their classmate. The type of research used in this study is quasi-experiment with pretest-posttest control group design. The Population of this study is 35 students. The method of data collection used is by questioner. The result of the analysis is (tcount0,063> ttable2,032) so that Ho is rejected and Ha is accepted. So there is a significant difference. It can be concluded that behavioral counseling with behavioral shaping technique is effective to increase the feeling guilty behavior when the student doing some mistake.